cDNA cloning of the constant region genes of the guinea pig α/β T-cell receptor - Schenkel, Johannes; Schäfer, Hubert; Baron, Udo; Müller, Beate; Burger, Reinhard (Developmental & comparative immunology, 1992)
A lambda gt11 cDNA library was prepared from activated guinea pig T-lymphocyte blasts. cDNA clones coding for the alpha-chain and beta-chain of the constant region of the guinea pig T-cell receptor were isolated by means of crosshybridization using the corresponding mouse cDNA genes. The guinea pig and the corresponding mouse cDNA genes hybridized in Northern blots with mouse mRNA of the same size. Guinea pig T-cell receptor mRNA showed the same size like its mouse counterpart. In contrast to the alpha-chain clone, genomic Southern blot analysis showed that the identified beta-chain gene fragment undergoes genomic rearrangement during T-cell differentiation.
Available online: 12 November 2002
Gesehen am 22.02.2021